3D web-based residential college system / Siti Sarah Mohamad Nor ... [et al.] - Mohamad Nor, Siti Sarah; Zulkefli, Nazrin Zulkhaini; Hashim, Hasranizam; Adnan, Nor Aizam (College of Built Environment, 2023)
The innovation product of the 3D interactive web-based residential college system is where the system utilized an advance technology of geospatial analysis (Geographical Information System).